Interweaving bonds: examining trust, commitment and social sustainability in the agri-food supply chain in Kenya - Edwin Obonyo; S. Wagura Ndiritu; Marco Formentini (Management Matters)
Purpose – The aim of this paper is to examine trust, commitment and social sustainability (SS) in agri-food supply chains (AFSCs) in an underexplored context, an emerging country. This adds to the literature on the benefits of trust and commitment in AFSCs. Design/methodology/approach – Within four counties in Kenya — Nairobi, Machakos, Kiambu and Kajiado — 85 abattoirs and 164 traders were surveyed as part of data collection. Hypotheses were proposed, and partial least squares structural equation modelling (PLS-SEM) was used to test them. Findings – The findings indicate that trust (benevolent and credibility trust) as well as commitment (affective and continuance commitment) have a positive direct relationship with SS. Practical implications – The study underlines how important trust and commitment are in improving the social well-being of AFSC actors. They enhance collaboration which empowers them to improve social welfare of the supply chain. Originality/value – The study is one of the first to examine the effect of trust and commitment on SS within AFSC, a novel contribution to SS literature. It differentiates between types of trust (benevolent and credibility trust) and commitment (affective and continuance commitment), giving a clearer understanding of how each of the variables impact SS. The findings offer new insights into the relationship between trust and commitment in improving social sustainable practices in AFSCs.